EKTRAKSI SILIKON DIOKSIDA DARI DAUN BAMBU - Halimah Sa'diyah; Salamet Nurhimawan; Sigit Ahmad Fatoni; Irmansyah Irmansyah; Irzaman Irzaman (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Silika extract has got from bamboo leaf by leaching with HCl 7% p.a. After bamboo leaf was burned, the charcoal was heated in the furnace with annealing rates of 0.9 and 1 °C/minute. The first temperature was room temperature, then increased to 400 °C with 2 hours arrested time. And last increased to 950 °C with 1 hour arrested time. The resulting ash was leached with HCl 7% p.a and its pH was neutralisted by aquabides. Then, the neutral ash was heated in furnace at 1000 °C. The result of EDX analysis showed that silica samples have purity levels of 84.53% to 99.99%. FTIR result showed that silica samples have absorption bands at wave numbers of 1071 cm-1, 1060 cm-1 and 798 cm-1 which indicate the asymetric stretching vibration of Si-O from siloxane group. Keywords: silica, bamboo leaves, purity level, function group.